Landscape and Englishness - Burden, Robert; Kohl, Stephan (Amsterdam ; New York, NY : Rodopi, 2006)
In the papers collected in this, the first volume of the Spatial Practices series, Englishness is reflected in the spaces it occupies or dwells in. Broadly influenced by a renewed and growing interest in questions of cultural identity, its emergence in Victorian theories and fictions of nationality, and the new cultural geography, the papers cover a rich variety of spaces and places which have been appropriated for cultural meanings: the rural countryside and farmland of the Home Counties in the early nineteenth century as Arcadian idyll in Cobbett, as the land to die for in war propaganda, an.
Landscape and Englishness; Contents; Notes on Contributors; Introduction: Englishness and Spatial Practices; Negotiating Englishness: Choropoetics, Reciprocal Spatial Realities and Holistic Spatial Semantics in William Renton's 'The Fork of the Road' (1876); The Vertical Axis in Landscape Description: Elaborations of the Image Schemas UP and DOWN; England's Domestic Others: The Tourist Construction of Agriculture and Landscape in William Cobbett's Rural Rides (1830); Character, Identity, and Nationality in the English Novel.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: England -- Historical geography; Cultural landscapes -- England; Landscapes -- Symbolic aspects -- England; National characteristics, English; Angleterre -- Géographie historique; Paysages culturels -- Angleterre; Paysages -- Aspect symbolique -- Angleterre; Anglais; HISTORY -- Historical Geography; Cultural landscapes; Historical geography; Landscapes -- Symbolic aspects; National characteristics, English; England; Electronic book